Central Biotherium of the Universidad Centroccidental "Lisandro Alvarado" (UCLA) during the COVID- 19 pandemic (Gaceta de Ciencias Veterinarias, 2021)
The times of the COVID-19 pandemic in the biotheriums have not been easy worldwide. Neither has it been so for the biotheriums in Venezuela, especially in the Central Biotherium of the Lisandro Alvarado Centroccidental University, which did not stop working 365 days of the year, 2019 or the subsequent years of Pandemic, at the beginning there was much fear on the part of the personnel working in the Unit, but it had to be clear that they were working with defenseless living beings that needed specialized human beings who worked in the unit to take care of them and maintain them. Several preventive measures were adapted in accordance with what the governmental authorities indicated. But they were adjusted to the unit's own needs, the main ones being the biosecurity measures to guarantee the well-being of the personnel working in the unit so that they in turn could guarantee the safety of their families, thus avoiding any contagion that could put the personnel's lives at risk. On the other hand, maintaining the safety of the animals produced in the Central Biotherium such as NMRI strain mice, C57Bl/6 strain, Sprague dawley strain rats, as well as Syrian Hamsters, guaranteeing their feeding, as well as cleaning and disinfection of the cages and facilities, which could certify their welfare. The production of animals was reduced to its minimum expression, keeping only the offspring of the strains of each species. Thus safeguarding the production of the animals produced in the Unit.
Keywords: biotherium; pandemic-Covid-19; laboratory animals